2014
DOI: 10.1177/1078155214551316
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination by cyclophosphamide preparation: Comparison of conventional manual production in biological safety cabinet and robot-assisted production by APOTECAchemo

Abstract: Compared to outcomes of other studies, our results underline good manufacturing procedures in this pharmacy with low contamination for both techniques (BSC and APOTECAchemo). Comparison of both preparation procedures validated that contamination of infusion bags was much lower by using the robotic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 16 publications
(17 reference statements)
0
46
0
Order By: Relevance
“…Recently, a wipe test investigated environmental and product contaminations by CPA in the robotic preparation with APOTECAchemo and manual preparation was published [16]. This report showed that the contamination of CPA was observed on the operator’s gloves (4 of 7: 0.0004-0.0967 ng/cm 2 ) and the majority (70%) of infusion bags during manual preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a wipe test investigated environmental and product contaminations by CPA in the robotic preparation with APOTECAchemo and manual preparation was published [16]. This report showed that the contamination of CPA was observed on the operator’s gloves (4 of 7: 0.0004-0.0967 ng/cm 2 ) and the majority (70%) of infusion bags during manual preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The first experiences in automated antineoplastic drug preparation have been published in 19902 and various experiences with fully automated robots followed more than one decade later,3 4 but approaches and local conditions that influence use and output of the device are different. In addition, there is already evidence that robotic devices are able to produce very low contamination levels,5 and therefore, might be capable of enhancing staff safety 6…”
Section: Introductionmentioning
confidence: 99%
“…Our results imply smaller contamination rates for both manual and robotic compounding than previous research did. Earlier studies suggested that variability in surface contamination could be associated with different methods of drug preparation, which can influence work techniques, that is proximity of the storage area relative to the preparation area, as well as the size of the compounding area where drugs are handled.…”
Section: Discussionmentioning
confidence: 41%
“…compared contamination with cyclophosphamide prepared using a manual procedure in a BSC to robotic‐assisted compounding using APOTECAchemo by measuring traces on the outside of prepared infusions. This study concluded that the total cyclophosphamide contamination was lower when the production was performed by the closed and controlled robotic system . Another study carried out by Iwamoto et al .…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation